X-ray photoelectron spectroscopy analysis of cotton treated with the TBCC/H2O2/NaHCO3 system. Issue 20 (December 2014) - Wang, Mengze; Long, Xiaoxia; Du, Jinmei; Sun, Chang; Fu, Shaohai; Xu, Changhai
N -[4-(triethylammoniomethyl)benzoyl]caprolactam chloride (TBCC) was used as a bleach activator for activation of hydrogen peroxide (H2 O2 ) in aqueous solution with the addition of sodium carbonate (NaHCO3 ). The TBCC/H2 O2 /NaHCO3 system was applied for treatment of cotton greige fabric at 60℃ in comparison with the conventional H2 O2 /NaOH system for treatment of cotton greige fabric at 95℃. Experimental results showed that the TBCC/H2 O2 /NaHCO3 system was effective for improving the degree of whiteness, reducing the fiber damage, and improving the water absorbency of cotton fabric. For understanding the treatment performance of the TBCC/H2 O2 /NaHCO3 system, X-ray photoelectron spectroscopy (XPS) was applied to analyze the surface elemental composition of cotton greige fabric before and after treatment. C 1s XPS spectra and quantitative analysis revealed that the TBCC/H2 O2 /NaHCO3 system improved the water absorbency of cotton fabric by removing hydrophobic matters as well as by oxidizing coloring matters and cellulose. The hexane extractions and scanning electron microscopy images indicated that the TBCC/H2 O2 /NaHCO3 system most likely removed the hydrophobic matters from cotton fabric in a "layer-by-layer" mode, which limited the cellulose backbones exposed for XPS analysis but allowed water to penetrate into cotton fibers.